Transcriptional analysis reveals that the intracellular lipid accumulation impairs gene expression profiles involved in insulin response-associated cardiac functionality - Actis Dato, Virginia (2023)
Cardiovascular disease (CVD) is a multisystemic and multicellular pathology that is generally associated with high levels of atherogenic lipoproteins in circulation. These lipoproteins tend to be retained and modifed, for example, aggregated low-density lipoprotein (aggLDL), in the extracellular matrix of diferent tissues, such as the vascular wall and heart. The uptake of aggLDL generates a signifcant increase in cholesteryl ester (CE) in these tissues. We previously found that the accumulation of CE generates alterations in the insulin response in the heart. Although the insulin response is mainly associated with the uptake and metabolism of glucose, other studies have shown that insulin would fulfll functions in this tissue, such as regulating the calcium cycle and cardiac contractility. Here, we found that aggLDL induced-lipid accumulation altered the gene expression profle involved in processes essential for cardiac functionality, including insulin response and glucose uptake (Insr, Ins1, Pik3ip1, Slc2a4 gene expression), calcium cycle (Cacna1s and Gjc2 gene expression) and calcium-dependent cardiac contractility (Myh3), and cholesterol efux (Abca1), in HL-1 cardiomyocytes. These observations were recapitulated using an in vivo model of hypercholesterolemic ApoE-KO mice. Altogether, these results may explain the deleterious efect of lipid accumulation in the myocardium, with important implications for lipid-overloaded associated CVD, including impaired insulin response, disrupted lipid metabolism, altered cardiac structure, and increased susceptibility to cardiovascular events.